2017
DOI: 10.1039/c6fo01615d
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two novel antioxidant peptides from edible bird's nest (Aerodramus fuciphagus) protein hydrolysates

Abstract: Edible bird's nest (EBN) is widely consumed as a delicacy and traditional medicine amongst the Chinese. In the present study, for the first time, the antioxidant properties of an EBN pepsin-trypsin hydrolysate of the swiftlet species Aerodramus fuciphagus and its ultrafiltration fractions were investigated. Thirteen peptides with molecular weights between 514.29 and 954.52 Da were identified in the EBN fraction with the use of mass spectrometry. Two novel pentapeptides Pro-Phe-His-Pro-Tyr and Leu-Leu-Gly-Asp-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 25 publications
4
45
0
1
Order By: Relevance
“…This is largely associated with the enzymatic hydrolysis process which hydrolysed glycoprotein, releasing bioactive peptides that were embedded in the EBN. This is supported by the study conducted by Ghassem et al 6 that antioxidant capacity (ORAC, FRAP, DPPH and ABTS assays) of EBN hydrolysate was greatly improved after the enzymatic reaction, as related with increased number of low molecular weight fractions that exhibited the highest propensity to scavenge free radicals. Based on the results, both processed cleaned EBN and EBN coproduct hydrolysates acted as good proton donors and reacted with free radicals to stop the reaction of radical chains.…”
Section: Antioxidant Activities Of Ebn and Its Hydrolysatesmentioning
confidence: 55%
See 1 more Smart Citation
“…This is largely associated with the enzymatic hydrolysis process which hydrolysed glycoprotein, releasing bioactive peptides that were embedded in the EBN. This is supported by the study conducted by Ghassem et al 6 that antioxidant capacity (ORAC, FRAP, DPPH and ABTS assays) of EBN hydrolysate was greatly improved after the enzymatic reaction, as related with increased number of low molecular weight fractions that exhibited the highest propensity to scavenge free radicals. Based on the results, both processed cleaned EBN and EBN coproduct hydrolysates acted as good proton donors and reacted with free radicals to stop the reaction of radical chains.…”
Section: Antioxidant Activities Of Ebn and Its Hydrolysatesmentioning
confidence: 55%
“…Traditionally, EBN is a well-known delicacy among the Chinese community, usually prepared as 'bird's nest soup' using double boiling method with addition of rock sugar, to be consumed as a supplement for human health enhancement. 4 Many studies have proved that EBN possesses pharmacological effects to human health such as antioxidant properties, 6 antihypertensive effect, 7 improve bone strength, 8 induce cell proliferation, 9 and others. Furthermore, sialic acid extracted from EBN has been reported to assist in the development of infant brain functions 10 and prevent virus infection by neutralizing the infection and inhibiting the agglutination of red blood cells caused by virus infection.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many peptides, such as LDEPDPL, NIQTDDFRT, AEERYP, and DEDTQAMP, have been isolated and proven to have strong antioxidant activities (Nimalaratne, Bandara, & Wu, 2015). However, researches on egg bioactive peptides has been only focused on the isolation of individual peptide with the highest antioxidant activity (Abeyrathne, Huang, & Ahn, 2018;Ghassem, Arihara, Mohammadi, Sani, & Babji, 2017) and the related methods are inapplicable to the food industry. Few studies have attempted to optimize the hydrolysis conditions for producing antioxidant peptides at a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…[43,[73][74][75]78] In another study, enzyme pancreatin F was used in the preparation of EBN glycopeptides to study the anti-viral activity. [13,62] A sequential pepsin-trypsin enzymatic hydrolysis was conducted by Ghassem et al [80] to produce bioactive glycopeptides from EBN extract and further evaluate radical-scavenging-linked antioxidant properties. The glycopeptides with strongest radical scavenging capacity were further purified through gel filtration and reverse phase-high performance liquid chromatography (RP-HPLC).…”
Section: Enzymatic Hydrolysis Methodsmentioning
confidence: 99%
“…[103] Histidine has also been proven to be an effective scavenger and metal ion chelator [104] ; while tripeptide containing tyrosine and tryptophan at C-termini shown to be strong radical scavengers. [105] Ghassem et al [80] have identified EBN glycopeptides with two peptide sequences of PFHPY and LLGDP, strongly corresponded to f134-138 and f164-168 of cytochrome b of swiftlet A. fuciphagus, based on the highest values of oxygen radical absorbance capacity (ORAC). The antioxidant efficacy of EBN was tested on the lifespan of fruit flies, Drosophila melanogaster.…”
Section: Undesirable Reaction During Production Of Ebn Bioactive Glycmentioning
confidence: 99%